(untitled) (International Journal of Engineering and Computer Science, 2015)
The rate of diffusion of knowledge management developmental systems in developed countries may now have reached the late majority phase of Rogers’ diffusion adoption model, given the large number of higher educational institutions that have adopted this technology for improving the quality of teaching and learning in the area of course delivery, quick access to information, operating costs reduction, information avalanche, online testing, quiz, online collaboration, submission of assignment, enhance feedback process, information consistency, self-study, on-demand course material availability and announcements to mention a few (Bhuasiri et. al, 2012). However, the rate of diffusion of this emerging technology in developing countries is still very slow (Bhuasiri et. al, 2012). For example , several institutions in Nigeria are not following this best practice in modern educational system, hence an in exhaustive exploratory case study was conducted at Imo State University using interview and questionnaire data generation methods to find out the barriers that might be impeding higher education in Nigeria from taking advantage of this educational technology break through. In addition, the study was conducted to identify enablers that may counter barriers and act as catalyst to enablers identified to increase the rate of adoption of this technology in developing countries.